Workforce Policy and Care Quality in English Long-term Elder Care. Issue 4 (2nd October 2018) - Atkinson, Carol; Crozier, Sarah; Lucas, Rosemary
Abstract: In this article, we explore workforce policy and its potential to improve care quality in English long-term elder care. Using large, secondary sector datasets, we analyze relationships between care quality and the skill development practices prescribed by workforce policy, care quality, and a wider set of employment practices. We demonstrate that the latter is more likely to improve care quality than skill development alone. We further demonstrate that both skill development/care quality and employment practice/care quality relationships are stronger in the statutory than the independent sector. Our findings challenge the effectiveness of workforce policy in two ways. First, it may be too narrowly focused on skill development at the expense of wider employment practice. Second, it may not be effective in improving care quality when outsourcing care ostensibly to improve it leads, particularly in the independent sector, to cost-based commissioning that mitigates against robust employment practice.